A case study on Salmonellaenterica serovar Typhimurium at a dairy farm associated with massive sparrow death. Issue 1 (December 2015) - Tamamura, Yukino; Uchida, Ikuo; Tanaka, Kiyoshi; Nakano, Yoshinori; Izumiya, Hidemasa; Takahashi, Tatsufumi; Kikuchi, Naoya
Abstract Background Salmonella enterica Typhimurium (S . Typhimurium) is the most common cause of bovine salmonellosis in Japan and where it is also cause of salmonellosis in wild birds. In 2008, a postpartum cow at a dairy farm developed diarrhea caused byS . Typhimurium. The herd was extensively surveilled forSalmonella sp. and we characterized bacterial isolates from this and other cows to determine the source of infection. Results Eight isolates ofS . Typhimurium from cattle were identified as phage type DT40 and showed a 100 % similarity by pulsed-field gel electrophoresis and the same or similar multiple-locus variable-number tandem-repeat analysis profiles as those ofS . Typhimurium isolated from dead sparrows (Passer montanus ) collected at Asahikawa in 2006.S . Typhimurium DT40 was considered to be a major cause of high sparrow mortality in Hokkaido in 2005–2006 and 2008–2009, suggesting that DT40 maintained in sparrows was transmitted to cattle. Conclusions S . Typhimurium DT40 may be transmitted from sparrows to dairy cattle.